A comparison of single-dose versus divided-dose of metronidazole on bacterial vaginosis among female sex workers in Surakarta - Damayanti, Willa; Hastuti, Rini; Triana, Agung; Yuliarto, Danu; Ayu, Ardelia Dyah; Ellistasari, Endra Yustin (UI Scholars Hub, 2021)
Background: Bacterial vaginosis (BV) is the most common vaginal infection in sexually active women. Metronidazole (MTZ) is still one of the recommended regimens for BV either as a single-dose or divided-dose. In addition to its affordability and availability, oral metronidazole also produces fewer adverse effects. This study aimedto determine the efficacy of single-dose versus divided-dose metronidazole for BV among female sex workers (FSWs) in Surakarta. Methods: A single-blind randomized clinical trial was conducted in Surakarta. FSWswith BV (⩾3 Amsel criteria) were enrolled. The subjects were grouped into two, and treated with MTZ either as a single-dose of 2 gr (single-dose group) or 500 mg twice daily for one week (divided-dose group). After two weeks, we performed second vaginal swabs and reassessed the Amsel criteria, complaints and adverse events. Results: Out of 75 FSWs, 30 (42%) were diagnosed with BV. The efficacy between two groups was not significantly different. However, patients in the single-dose group were 2 times more likely to develop recurrent BV (OR = 2.000; 95% CI 0.146 – 27.447), and 1.5 times more likely to have vaginal discharge complaints (OR = 1,500; 95% CI 0,181-12,459) than divided-dose group. Conclusion: Single-dose and divided-dose metronidazole produce similar efficacy for treating BV in sexually active women. Single-dose metronidazole has a higher risk of BV recurrence and vaginal discharge complaint. Divided-dose metronidazole is recommended for treating BV.